1983
DOI: 10.1508/cytologia.48.749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some systemic fungicides on the chiasma frequencies in Hordeum vulgare.

Abstract: Modern agriculture has introduced a large number of pesticides into the environment. Some of these were demonstrated to exert toxic influences on various non-target organisms including plants (Mrak 1969 , Epstein andLegator 1971). In higher plants there were reported on the pesticide influences on mitosis and meiosis (Wuu andGrant 1966, 1967). However , it was not investigated whether or not the recombinant source of variation in meiosis was affected . To enquire such a possibility four systemic fungicides are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Between the temperature extremes at which meiosis fails altogether, environmental variation also causes variation in crossover frequency, which has important implications for models of the evolution of recombination as well as for population genetics and breeding (Otto & Michalakis, 1998;Otto & Barton, 2001;Marais & Charlesworth, 2003;Roze & Barton, 2006). The range of biotic and abiotic environmental factors known to affect crossover rates is remarkably broad and includes temperature, nutrient availability, fungicide application, pathogen attack, droughtand, in grasshoppers, even swarming (Grant, 1952;Law, 1963;Nolte, 1968;Bennett & Rees, 1970;Fedak, 1973;Sharma et al, 1983;Choudhary & Sajid, 1986;De Storme & Geelen, 2014). This begs the question why so many diverse environmental inputs affect meiosis.…”
Section: Environmental Effects On Crossover Numbermentioning
confidence: 99%
“…Between the temperature extremes at which meiosis fails altogether, environmental variation also causes variation in crossover frequency, which has important implications for models of the evolution of recombination as well as for population genetics and breeding (Otto & Michalakis, 1998;Otto & Barton, 2001;Marais & Charlesworth, 2003;Roze & Barton, 2006). The range of biotic and abiotic environmental factors known to affect crossover rates is remarkably broad and includes temperature, nutrient availability, fungicide application, pathogen attack, droughtand, in grasshoppers, even swarming (Grant, 1952;Law, 1963;Nolte, 1968;Bennett & Rees, 1970;Fedak, 1973;Sharma et al, 1983;Choudhary & Sajid, 1986;De Storme & Geelen, 2014). This begs the question why so many diverse environmental inputs affect meiosis.…”
Section: Environmental Effects On Crossover Numbermentioning
confidence: 99%
“…The mean chiasma frequency in each of three cultivars was significantly reduced to 2–4% lower than the control. A later study in the same species showed that the systemic fungicides fuberidazole, carboxin, and oxycarboxin (but not thiabendazole) all significantly reduced chiasma frequency ( Sharma et al, 1983 ). Carboxin and oxycarboxin has an effect even at the lowest concentration tested.…”
Section: Pesticidesmentioning
confidence: 94%